(untitled) (Communications in Computational Physics, 2010)
Non-local thermodynamic equilibrium (NLTE) conditions are universal in laboratory and astrophysical plasmas and, for this reason, the theory of NLTE plasmas is nowadays a very active subject. The populations of atomic levels and radiative properties are essential magnitudes in the study of these plasmas and the calculation of those properties relies on the so-called collisional-radiative (CR) models. However, the complexity of these models has led to the development of numerous collisional-radiative codes and this is a current research topic in plasmas. In this work is presented a versatile computational package, named ABAKO/RAPCAL, to calculate the populations of atomic levels and radiative properties of optically thin and thick, low-to-high Z, NLTE plasmas. ABAKO/RAPCAL combines a set of analytical approximations which yield substantial savings in computing running time, still comparing well with more elaborated codes and experimental data. In order to show the capabilities of the code and the accuracy of its results, calculations of several relevant plasma magnitudes for various plasma situations are shown and compared.